Connecting with your audience: delivering your best - Bandler, John; Ho, Rachelle; Ogrodnik, Michelle; Tajik, Daniel (Bandler Corporation, 2021)
Your ability to inspire and engage broad audiences beyond your usual “captive” technical and academic audiences is vital but challenging. To kindle curiosity and to fire up your non-specialist online “virtual” or video viewers with your research is harder still. Transferrable to virtually any professional career path, however, these communication skills become lifetime assets. We address the art of presenting complex research to general audiences, suggesting do’s and don’ts, with a focus on brief, one-minute, and three-minute presentations: pre-recorded, virtual or in person. The disorienting “virtual” medium we face daily is fraught with technical and physical limitations, surprises, and wrong assumptions, easily leading you astray, e.g., from a professional posture; you are subject to a physical disconnect from your audience and slides. Via this medium or delivering your video to any screen, you beg comparison with professionally produced content. We discuss storytelling, first impressions, citation, subtext, authenticity, articulation, slide design, script design, staging, stage presence, respecting your audience, and avoiding various traps and pitfalls. Through diverse case studies, including a Q&A with 3MT® winners and finalists online from Canada, the US, and the UK, we aim to give you the tools and strategies to deliver your best.
Bandler and co-presenters Ho, Ogrodnik, and Tajik delivered this webinar via Zoom, Feb. 18, 2021 in support of the GRADflix competition organized by the School of Graduate Studies, McMaster University. Diverse case studies include a Q&A with 3MT® winners Aline Eid and Mahmoud Wagih from the US and UK, respectively. Bander also analyzes Waterloo’s winning GRADflix video by Anna Murynka. This webinar is available on YouTube at https://www.youtube.com/watch?v=hJTskhBgDnw and https://www.youtube.com/watch?v=YPuw5PmNglk
Keywords: story; persuasion; bias; trust; impact; fear; first impressions; citation; subtext; metaphor; theatricality; authenticity; articulation; etiquette; awareness; being remembered; slide composition; respecting your audience; elevator pitch; ethics; admitting setbacks; Three Minute Thesis; 3MT; GRADflix; Zoom presentations; virtual presentations; science communication